A dendroclimatological study of east- and west-facing slopes in mountainous areas subjected to strong air pollution (the Sudetes, Central Europe). (4th March 2019) - Opała-Owczarek, Magdalena; Błaś, Marek; Owczarek, Piotr; Sobik, Mieczysław; Godek, Michał
ABSTRACT: The Sudetes Mountains (Central Europe) were under a particularly intense long-term air pollution load during the 1970s and 1980s. Intense industrial activity in this area led to large-scale forest dieback and reductions in tree growth rates, potentially limiting the use of tree-ring data from this region in dendroclimatic research. In this paper, ring-width chronologies were constructed for 493 Norway spruce trees ( Picea abies L. Karst.) from 17 sampling sites within five major mountain ranges in the Sudetes Mountains of Poland. Growth-climate response data indicate that April‒July temperatures are the main factor affecting radial growth of trees in the study area. Our data also indicate the strong influence of slope aspect on temperature signal strength. The lowest correlation values were obtained for sites located on western slopes with effective fog deposition, which are strongly affected by pollution. An appropriate sampling strategy resulted in the creation of a temperature-sensitive proxy record (rAMJJ = 0.70), exceptional for areas under strong pressure from human activity. Based on a regional master chronology, growing season (April‒July) temperatures over the past 200 years were then reconstructed. Four warm and four cold periods were distinguished and compared with other reconstructions and long-term instrumental data.